Investigation of host innate antiviral mechanisms that block replication of influenza A virus and coronaviruses - Al-Beltagi, Sarah El-Sayed Abd El-Wahab (2025)
Influenza A virus (IAV) and coronaviruses, including OC43 and SARS-CoV-2 variants, are RNA respiratory viruses that pose a substantial global health challenge due to their high transmissibility, potential for severe illness, and risk of co-infections. Despite the availability of vaccines and antiviral treatments, the continuous emergence of viral variants and resistance mechanisms underscores the urgent need for innovative host targeted antiviral therapies, which are less likely to induce viral revertants. Increasing evidence supports the antiviral activity of thapsigargin (TG), an inhibitor of the sarcoplasmic/endoplasmic reticulum (ER) Ca2+ ATPase pump and an inducer of ER stress, against a variety of viruses, including tick-borne encephalitis virus (TBEV), foot-and-mouth disease virus (FMDV), and IAV. However, the precise antiviral mechanisms of TG remain to be fully elucidated. The aim of this thesis was to investigate the potential antiviral mechanisms of TG against IAV, OC43, and SARS-CoV-2 variants. The first objective was to assess how TG influences the replication of these viruses. TG was found to inhibit these viruses at various stages of their life cycles; with post-translational inhibition observed for IAV, and transcriptional inhibition for OC43 and SARS-CoV-2 variants. The second objective focused on evaluating the induction of ER stress-related genes, both under basal conditions and during IAV, OC43, and SARS-CoV-2 infections. qPCR analysis revealed that TG increased the expression of ER stress-related genes both basally and during IAV, OC43, and SARS-CoV 2 infections. Furthermore, TG demonstrated extended antiviral activity accompanied with activation of ER stress response during OC43 and SARS-Cov-2 infections. The third objective was to examine the activation of the host innate immune response both basally and during IAV, OC43, SARS-CoV-2 infection using qPCR. TG enhanced early but also regulated activation of innate immune response. Moreover, in a preliminary study to evaluate if TG induces paracrine antiviral effect between macrophages and epithelial cells, supernatants from TG-treated macrophages, when used to prime epithelial cells, effectively inhibited SARS-CoV-2 infection. The final objective was to investigate the impact of TG on ER-synthesized IAV proteins— HA, NA, and M2—in both pig and human cells, and to elucidate TG's antiviral mechanisms on cellular processes exploited by these IAV proteins, including ubiquitination, glycosylation, autophagy, and their influence on virus morphology and budding. This objective was achieved using various techniques such as western blotting, immunofluorescence, a ubiquitin enrichment kit, a glycoprotein isolation kit, and transmission electron microscopy (TEM). It was found that TG induces cell-type specific effects on ER-synthesized IAV HA, NA, and M2 proteins. In human cells (A549), TG reduced the production of HA, NA, and M2 viral proteins and caused their accumulation in the perinuclear region compared to controls. In contrast, in pig cells (NPTr), TG did not affect the production or subcellular localization of HA, NA, and M2 viral proteins. In A549 cells, TG-induced M2 reduction was accompanied by a reduction in LC3 II levels, i.e. a decrease in autophagy, and absence of M2 ubiquitination. While, in NPTr cells, TG did not influence M2 protein production, which exhibited a notable double-band pattern. This TG-induced double banding of M2 was associated with (1) reduced co-localisation between M2 and LC3, (2) interference with M2 ubiquitination, (3) reduced M2 levels in the supernatant, and (4) a reduction in the length of the filamentous virus produced. Similarly, TG induced a double banded pattern for NP protein, a cytoplasmic-synthetized IAV protein, in both A549 and NPTr cells. Moreover, HA2 of HA and NP glycosylation was reduced by TG in NPTr cells. Consequently, in both A549 and NPTr cells, TG disrupted the assembly of viral proteins into new virions, as evidenced by a reduction in the quantity of IAV proteins (NA, HA, NP, M1, M2) present in the supernatant. This was accompanied by a decrease in viral RNA and infectious virus particles released, without affecting virus budding or causing significant changes to virus morphology. In conclusion, the findings demonstrate TG’s potential as a broad-spectrum antiviral against these viruses, acting through multiple mechanisms that target critical host pathways. TG induces several antiviral mechanisms, thus it offers a promising strategy for targeting other RNA viruses that similarly exploit these pathways during replication. However, further research is required to explore TG's efficacy as a host-targeted antiviral across a wider range of RNA viral pathogens and to assess its therapeutic potential in vivo.